Identifikasi dan Deteksi Aktivitas Daya Hambat Bakteri Actinomycetes yang diisolasi dari Tanah Gambut di Desa Tajok Kayong Kalimantan Barat - Rikhsan Kurniatuhadi, Sri Lestari, Mukarlina (Jurnal Protobiont, 2019)
Actinomycetes bacteria can grow well in soil media with acidic pH conditions such as peat soil. This study aims to determine the genus of Actinomycetes bacteria from peat soil. Sampling was done in Tajok Kayong Village, Ketapang Regency. Isolation was carried out using Pour Plate Method using specific media, namely SCA (Strach Casein Agar) media, while the activity detection of Actinomycetes bacteria was carried out on Eschericia coli pathogenic bacteria and Staphylococcus aureus using the streak-cross Method. Identification and Â characterization done it macroscopic, microscopic and biochemical. The results obtained 7 isolates of Actinomycetes bacteria from peat soil which is the genus Streptomyces.